El registro paleontológico y arqueológico de los yacimientos de la Trinchera del Ferrocarril en la Sierra de Atapuerca - Aguirre, Emiliano; Van der Made, Jan; Bastir, Markus; Fernández Jalvo, Yolanda; Huguet, Rosa; Laplana, César; Marquez, Belén; Martínez, Cayetana; Martinón, María; Rodríguez, Jesús; Sánchez, Antonio; Sarmiento, Susana; et al. (Coloquios de Paleontología, 2003)
The paleontological and archaeological record of the localities of the Trinchera del Ferrocarril represents key periods in the biological and cultural evolution of man, as well as in faunal, environmental and climatic history of Europe. The lower part of the sequence of Sima del Elefante (TE8-14) is around 1 Ma old and yielded indications of the presence of humans in the form of lithic industry and cutmarks. This time marks the onset of a series of fundamental climatic, environmental and faunal changes. The lower part of the Gran Dolina sequence (TDW4-TD8inf) straddles the Early - Middle Pleistocene limit, and its macro and micro fauna permits a very precise characterisation of the faunal and environmental events around this transition. Level TD6 yielded an abundant collection of remains of Homo antecessor. The archaeological record, including Mode 1 industry, cutmarks etc., provides a rare opportunity to study human behavior of this period. Galería (TG) and the upper part of the Gran Dolina sequence (TD10-11) belong to the central part of the Middle Pleistocene and have an abundant palaeontological and archaeological record, including remains of Homo heidelbergensis and Mode 2 and 3 industry.